In Silico Analgesic and Toxicity Analysis of Modified Paracetamol on COX-2 Receptor (PDB ID: 3LN1) - Hidayah, Nurul; Lina Permatasari; Agriana Rosmalina Hidayati; Handa Muliasari (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2024)
Background: Paracetamol is often used as the main analgesic in Indonesia. The use of more than 4 g/day or a single dose above 10 g can cause hepatotoxicity. This can be overcome by modifying the structure through a computer-aided drug design (CADD) approach, particularly molecular docking, which aims to produce compounds with greater potency and fewer side effects. Objective: This study aimed to determine the analgesic activity and toxicity of paracetamol derivatives modified using the Topliss method. Methods: Analgesic activity was tested by molecular docking of the COX-2 receptor (PDB ID 3LN1) using AutoDock Tool 4.2 and toxicity testing using pkCSM and Protox Online Tool. Results: The results of docking showed that the free binding energy values ​​for test compounds 1 to 5 are -10.59 kcal/mol, -10.17 kcal/mol, -8.79 kcal/mol, -10.01 kcal/mol, and -9.32 kcal/mol, respectively, with corresponding inhibition constants of 17.29 nM, 35.21 nM, 360.88 nM, 46.36 nM, and 146.65 nM. These values are lower than paracetamol, which has a free binding energy of -6.21 kcal/mol and an inhibition constant of 28,043 nM. The results showed that the test compound was more stable in ligand-receptor binding. Toxicity tests showed that all the test compounds and paracetamol belonged to toxicity class IV. The test compound had an LD50 value of 1551 mg/kg, which was higher than that of paracetamol (338 mg/kg), indicating better effectiveness. Conclusions: Compound 2 was predicted to have the best biological activity and potential as an alternative to paracetamol.